Digital Education and Artificial Intelligence: Attitudes and Readiness of Economics Teachers in Greece - Angelos Stoumpos; Rodanthi Stoumpou; Vassilis Tsiantos (Yayasan Al Hidayah, 2026)
The rapid development of digital technology and artificial intelligence, combined with their rapid integration into education, is transforming educational processes and methods worldwide. This study investigates the attitudes, familiarity, and experiences of economics teachers in Greece regarding the use of digital tools and artificial intelligence. Using the snowball method, a structured electronic questionnaire was distributed and 100 valid responses were collected from active economics teachers. Factor analysis revealed two key dimensions: (1) attitudes and perceived benefits of artificial intelligence and digital technologies in education, and (2) familiarity and technical skills in using these tools. The results show that teachers recognize the potential of artificial intelligence to contribute to improving learning, student engagement, and the development of 21st-century skills. At the same time, they point out the need for appropriate training and support for its effective implementation. The reliability of the questionnaire was confirmed by a high Cronbach's Alpha index (0.948), and the findings provide important information for policies and practices of digital transformation in economics education.